«ЖӘҲАНША» ДӘСТАНЫНЫҢ ЖАЗЫП АЛЫНЫЎЫ ҲӘМ ИЗЕРТЛЕНИЎИ МӘСЕЛЕЛЕРИ - Мамбетов, Ж.Қ. (SCIENCE and SOCIETY, 2021)
This article deals with the recordings, publication and research of the Karakalpak folk epic "Jahansho" from Kurbanboy Jirov. There is information about the history of the study of the epic "Jahansho". Scientific research ideas and conclusions are analyzed.